The lemon tree : an Arab, a Jew, and the heart of the Middle East - Tolan, Sandy (Bloomsbury Children's Books, 2020)
Provides a young reader's adaptation of the true story of the friendship between Palestinian Bashir Khairi and Israeli Dalia Eshkenazi Landau that develops because their families both lived in the same home. In 1967, twenty-five-year-old refugee Bashir journeys from Ramallah to Israel to see his former home, with a lemon tree in the backyard, that he was forced to leave during the Six-Day War. There he encounters nineteen-year-old Dalia, an Israeli college student whose family had been devastated by the Holocaust. The two become friends and manage to maintain their friendship as both the Israelis and the Palestinians fight over the land.